Upaya Meningkatkan Kemampuan Menulis Surat Pribadi Melalui Metode Pembelajaran Peta Konsep Pada Siswa Kelas IV SD Negeri 008 Tambusai Utara Tahun Ajaran 2013/2014 - Ramida Ramida (STKIP Rokania Pasir Pangaraian, 2018)
One of the objectives of learning on Personal Letter material is that students are able to write personal letters well. However, the goal is a difficult problem for the fourth grade of SD N 003 Tambusai Utara, Teachers are still tied to traditional and monotonous learning patterns. Conditions such as these can hinder students to be active and creative resulting in poor quality of students. Learning systems with traditional approaches that are still applied by teachers are not able to create coveted students, especially for the field of personal letter writing skills. Learning with the concept map method (Mind Mapping) is a new concept. The concept map method (Mind Mapping) is a creative note method that allows us to remember a lot of information. The concept of learning is what is expected to overcome difficulties in writing a personal letter. The final result of this research is with very specific problem that is the behavior of lack of writing skill of Personal Letter, hence in process and time period which is not short, concept learning method have positive impact for student that is student that can improve the ability of writing personal letter. Proven on the acquisition of student learning outcomes that continue to increase from pre cycle to cycle 2. In pre cycles in which the learning is still using the lecture method students who can tubtas learn only a number of 10 students, then in the first cycle of researchers apply the conceptual learning method, and the results of cycle 1 is there are 17 students who complete learning. In cycle 2 is still with conceptual learning method of learning then all students of Class IV which amounted to 27 students can achieve mastery learning